2006
DOI: 10.1002/aqc.793
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical water requirements of the white‐clawed crayfish (Austropotamobius pallipes) in western France

Abstract: ABSTRACT1. In France, the distribution of the native white-clawed crayfish (Austropotamobius pallipes) is restricted, fragmented and mainly located in headwater streams. To conserve this indigenous species, it is necessary to characterize its habitat preferences.2. Seven brooks in the Deux-Se`vres De´partement (western France) containing wild populations of A. pallipes were studied to determine its ranges of tolerance to 19 physical and chemical water parameters. On two brooks, the Se`vre Nantaise and the Verd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 24 publications
9
50
2
Order By: Relevance
“…This decline is due to causes frequently linked to direct human action, such as habitat fragmentation, deforestation and water deterioration (Nardi et al, 2005;Trouilhe et al, 2007;Favaro et al, 2010). Consequently, the species is listed in the EU Directive 92/43/EEC, commonly known as Habitat Directive (Annex II and V) and it is also listed as endangered by the IUCN (Füreder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This decline is due to causes frequently linked to direct human action, such as habitat fragmentation, deforestation and water deterioration (Nardi et al, 2005;Trouilhe et al, 2007;Favaro et al, 2010). Consequently, the species is listed in the EU Directive 92/43/EEC, commonly known as Habitat Directive (Annex II and V) and it is also listed as endangered by the IUCN (Füreder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Populations of A. pallipes have been found in water with potassium concentrations similar to those of mean global and European waters (Figure 1d) with two studies finding populations associated with concentrations in the lower ranges of global and European means (Rallo and Garcia-Arberas, 2002;Trouilhé et al, 2007). Given the wide range of potassium concentrations found in waters inhabited by A. pallipes, no association for specific potassium concentrations can be identified.…”
Section: > Potassium [K + ]mentioning
confidence: 94%
“…However, several studies (e.g. Trouilhé et al, 2007) also found populations to persist at concentrations lower than the means cited for European rivers. It appears that there may be a lower threshold for dissolved oxygen concentration below which crayfish are not found (i.e.…”
Section: > Oxygen (Do)mentioning
confidence: 97%
“…Demers and Reynolds (2002), for example, has shown that, in Ireland, A. pallipes can be found in moderately polluted waters. More recently, Trouilhé et al (2007) found that in France this species is able to tolerate wide ranges in the value of some physico-chemical water parameters: the site that harbored the largest A. pallipes population of the study (17.5 crayfish·m −2 ) had dissolved oxygen concentrations as low as 4.93 mg·L −1 , while water temperature rose above 20 • C for several consecutive days during summer and nitrate concentrations were always found to be above 30 mg·L −1 .…”
Section: Indirect Use As Surrogate Speciesmentioning
confidence: 99%